F (x) = 2x + 3; find f (–1)" (pronounced as "f-of-x equals 2x plus three; find f-of-negative-one"). In either notation, you do exactly the same thing: you plug –1 in for x, multiply by the 2, and then add in the 3, simplifying to get a final value of +1
Answer: 9
Step-by-step explanation:
Answer:
y=5x+3
Step-by-step explanation:
I learned it in school :)
Answer:
6
Step-by-step explanation:
base + 2(legs) = 56 (2 legs are the same because it's isosceles)
x + 2(5x - 5) = 56
x + 10x - 10 = 56
11x -10 = 56
11x = 66
x = 6
Answer:
9/10
Step-by-step explanation:
90%